Kualitas Pelayanan Kesehatan di RSUD Kabupaten Sidoarjo - Mursyidah, Lailul; Nurfajriyah, Islamic (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this study to discribe the quality of health care at Sidoarjo Hospitals, exactly outpatient of iclinic executives and to determines the factors that inhibiting the implementation of health care for outpatient of clinic executive. This study used a Descriptive Qualitative Method. Technique of deciding informant by snowball sampling. Primary data were obtained by in-depth interviews with key informants head room of installation pavilion Sidoarjo Hospital, two nurse of executive polyclinic Sidoarjo hospital and 12 patient and patient's family of polyclinic executive Sidoarjo hospital are as informants. The results showed that the quality of health care at policlinic executives by perseption of respondents in terms of five dimensions of service quality models ServQual include dimensional visibility physical (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy) overall get a positive response from community. Factor that inhibiting implementation of service quality are a lack of medical personnel (nurses) at the policlinic executives, so they have to do multi task at a same time. There are unavailable fix doctor schedule and medical facilities not integrated yet has been the factors that inhibit the implementation of health care of clinic executives too.